إستراتيجية المعلم الفعال في العملية التربوية - أعـمر, فضيلة; غنبازة, جمال (University of Eloued جامعة الوادي, 2020)
يعد المعلم من أهم عناصر العملية التربوية ،فهو القادر على تحقيق أهداف التعليم و ترجمتها إلى واقع ملموس،و هو الذي يعمل على تنمية القدرات و المهارات لدى التلاميذ عن طريق تنظيم العملية التعليمية و ضبطها و إدارتها و استخدامها تقنيات التعليم و وسائله ، ومعرفة حاجات التلاميذ و طرائق تفكيرهم و تعلمهم و تحديد أهداف التربية في تطوير المجتمع و تقدمه، فقد عرف المعلم بمهندس العملية التعليمية كصانع للقرار و القادر على مواكبة المستجدات السريعة في التكنولوجيا الحديثة، و القادر على تعلم الأساليب الحديثة في التدريس و الاستراتيجيات الفعالة و التعمق في فهم فلسفتها و إتقان تطبيقها، و المتمكن من نقل هذا الفكر إلى تلاميذه فيمارسونه من خلال أدوات التعليم بتقنيات تربوية ، و إلى جانب هذا فان التعليم بتقنيات تربوية ليس مجرد برمجيات و عتاد و أجهزة مبهرة ، بل هو في الدرجة الأولى ، و من هنا تأتي الحاجة المستمرة إلى مراجعة لما تقدمه مؤسسات التعليم. لذا فان البحث يرمي إلى التعرف على أهمية المعلم و دوره في تطوير المناهج الدراسية باستخدام التقنيات التربوية Abstract : The teacher is one of the most important element of the educational process ,he is able to achieve the goals of education and translate them into reality ,he works to develop the abilities and skills of students through organizing ,controlling ,managing techniques and means , knowing the neads of students and ways of thinking and learning and defining the objectives of society ,the teacher was know as the architect of the educational process as a decision-maker and able to keep pace with the rapid developments of modern technologies , he is able to learn modern methods of teaching effective strategies and deeper understanating of its philosophy and mastery of its application. The teacher is able to transfer this thought to his pupils and practising through educational techniques .In addition ,education with educational techniques is not just software ,hardware and impressive equipment it is a first class .It is first and foremost the constant need to review what education institutions offer .There fore ,the research aims identify the importance of the teacher and his role in the development of the curriculum using educational techniques.
Effective teacher strategy in the educational process
الملتقى الوطني الأول حول المدرسة الجزائرية الإشكالات والتحديات 18- 19 فيفري 2020. جامعة الوادي
Keywords: المعلم ، المعلم الفعال،المقاربة بالكفاءات; The teacher ,effective teacher ,competency approach